Good practice : communication skills in English for the medical practitioner : student's book. - McCullagh, Marie, ....-; Wright, Ros, ....- (Cambridge : Cambridge University, 2008)
Good Practice is a course for doctors and medical students who need to communicate with patients in English, and can be used in the classroom or for self-study. Good Practice focuses on the language and communication skills that doctors need to make consultations more effective through a focus on five elements of good communication: verbal communication, active listening, voice management, non-verbal communication and cultural awareness. The course teaches learners how to sensitively handle a range of situations such as taking a patient history, breaking bad news, examining a patient and describing treatment options, as well as preparing doctors for dealing with different types of patients, from children to the elderly. With reference to numerous medical communication experts, and through exposure to authentic clinical scenarios, the course demonstrates the impact of good communication on the doctor-patient relationship and enables students to become confident and effective practitioners in English.
Keywords: Engels -- Taalgebruik -- Geneeskunde